PLANNING AND WORKING MEMORY EFFECTS ON L2 PERFORMANCE IN CHINESE EFL LEARNERS’ ARGUMENTATIVE WRITING - Yi, Baoshu; Ni, Chuanbi (Universitas Pendidikan Indonesia, 2015)
With the guidance of Skehan’s cognitive model of L2 performance and Kellogg’s model of working memory in writing, the present study explored the effects of planning and working memory on L2 performance in Chinese EFL learners’ argumentative writings. The participants were required to complete one operation span task and two argumentative essays in pre-task planning and controlled conditions (no planning). Results showed that: 1) pre-task planning seemed to help a significant increase of lexical complexity in L2 writing performance; 2) working memory had a significant impact on syntactic complexity and fluency but no effect of working memory was found on lexical complexity and accuracy; 3) pre-planning could be integrated with working memory to affect L2 writing performance. In argumentative writings, working memory might be of great importance in planning while planning might enable learners to overcome limitations in working memory and enhance L2 writing performance.